2010
DOI: 10.2298/vsp1007573j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, hemoglobin content, superoxide dismutase and catalase activity influenced by sulphur baths and mud packs in patients with osteoarthritis

Abstract: A combined 3-week treatment by sulphur bath and mud packs led to a significant decrease of lipid peroxidation in plasma, as well as pain intensity in the patients with OA. These changes were associated with changes in plasma activity of SOD and CAT and a significant increase of hemoglobin level suggesting their role in beneficial effect of spa therapy in the patients with OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…In vivo, reductions in serum levels of malondialdehyde (MDA) and carbonyls, and in SOD and catalase activity [ 45 , 110 , 111 ], have been found after balneotherapy with sulfurous water in rheumatic diseases, thus reflecting a reduction in oxidative stress that may contribute to reduce the inflammatory and catabolic status. Indeed, sulfurous waters are clinically effective in the treatment of OA and RA patients [ 112 , 113 ].…”
Section: Balneotherapy As a Hormetic Strategymentioning
confidence: 99%
“…In vivo, reductions in serum levels of malondialdehyde (MDA) and carbonyls, and in SOD and catalase activity [ 45 , 110 , 111 ], have been found after balneotherapy with sulfurous water in rheumatic diseases, thus reflecting a reduction in oxidative stress that may contribute to reduce the inflammatory and catabolic status. Indeed, sulfurous waters are clinically effective in the treatment of OA and RA patients [ 112 , 113 ].…”
Section: Balneotherapy As a Hormetic Strategymentioning
confidence: 99%
“…Jokić et al showed that treatment with sulfur and peloid baths in patients with hip and knee osteoarthritis led to a significant reduction in plasma lipid peroxidation and changed plasma activity of superoxide dysmutase and catalase. A significant increase in the hemoglobin level was observed, which was assumed to be a result of inhibited production of excess free radicals [ 20 ]. The study by Zinchuk et al showed that dry sauna causes a drop in the hemoglobin level.…”
Section: Discussionmentioning
confidence: 99%
“…Der positive Einfluss einer Heiltorftherapie auf molekularer Ebene konnte bisher in einigen Studien bei degenerativen Gelenkerkrankungen nachgewiesen werden: Bei Arthrosepatienten war eine Abnahme des proinflammatorischen TNF-α [20,21], eine Verminderung von TNF-α Rezeptoren [22], eine Reduktion von IL-1 Spiegeln [23], ein Abfall von Prostaglandin E 2 (PGE 2 ) und von Leukotrien (LTB 4 ) [24] sowie eine Modulation der Produktion von Metalloproteinasen [25,26] nachweisbar. Vergleichbare Ergebnisse auf molekularer Ebene durch Heiltorftherapie fanden sich in 2 weiteren Studien bei humaner Arthrose [27,28].…”
Section: Molekulare Marker/zytokine Laborchemische Krankheitsaktivitätunclassified